The impact of L2 German on component processes of reading. (21st July 2016) - Schröter, Pauline; Schroeder, Sascha
Abstract : Background: In Germany, there is a substantial gap in reading literacy between monolingual children and their L2‐speaking peers. Nevertheless, it is still unclear where these performance differences are rooted. Methods: We investigated children of grades 5, 6 and 7 with comparable socio‐economic status, who completed a battery of tests assessing their linguistic and executive functioning skills as well as their reading performance on the letter, word, sentence and text level. Results: Whereas L1 speakers showed better linguistic skills, there was no difference between groups in executive functioning. After controlling for individual differences on each level of reading, groups only differed in text comprehension. This effect, however, disappeared when participants' linguistic skills were additionally controlled. Conclusions: In sum, results show that reading problems in L2 speakers cannot be attributed to deficits on specific component processes of reading, but to a lack of linguistic skills, which negatively affects reading comprehension.